(untitled) (Revista Linhas, 2007)
Este artigo propõe-se a fazer uma diferenciação e a análise da avaliação sob as óticas “qualitativas” e “quantitativas” reconhecendo a avaliação como um ato político. Tece também algumas considerações a respeito da avaliação libertadora e, do seu papel em nossa sociedade. Palavras-chave:avaliação, processo político pedagógico. Abstract:This article intends to do a differentiation and an analysis of the evaluation under the “qualitative” and “quantitative” optics, recognizing the evaluation as a political act. It also shows some considerations about the liberating evaluation and its role on our society. Key-Words:evaluation, political-pedagogic process.